PENGARUH CAREER SUCCESS TERHADAP CAREER CRAFTING DENGAN LEARNING VALUE OF THE JOB SEBAGAI VARIABEL MODERASI - Ika Ayu Sintawati; Dwiarko Nugrohoseno (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to test and analyze the effect of career success on career crafting with the learning value of the job as a moderating variable. The approach used in this study was quantitative. A survey was conducted among a sample of 77 employees. The data in this study were analyzed using the structural equation model partial least squares (SEM-PLS) with WarpPLS 8.0 software. The results show that objective career success has no effect on career crafting, subjective career success has a significant positive impact on career crafting, the moderating role of the learning value of the job weakens objective career success on career crafting, and the part of the learning value of the job does not moderate subjective career success towards career crafting. The implications based on the research results show that it is essential for companies to pay more attention and act to the sustainability of the perceived career success, both objective and subjective, and also learn the value of their employee's jobs to foster their proactivity career behaviours.